Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing - Pérez-Ramos, Ignacio M.; Urbieta, Itziar R.; Marañón, Teodoro; Zavala, M. A.; Kobe, Richard K. (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: plant cover (voyant); Quercus canariensis; Quercus suber; Seed removal; Seed size